Redistribution and the efficiency of the pay-as-you-go pension system - Johann K. Brunner (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1993)
The paper considers the efficiency of the pay-as-you-go pension system with endogenous labor supply, when contributions are collected as an income tax. Results from the literature state that in this case a Pareto-improving transition path to a fully-funded system exists, if the interest rate is permanently higher than the growth rate of the economy. It is shown that these results depend crucially on the possibility of replacing the income tax by a lump-sum tax. If one adopts the realistic assumption that such a change is impossible, no Pareto-improving transition path from an unfunded to a funded pension system exists.
Keywords: 330; social security; income taxation; redistribution